The discovery saga collection : a 6-part series from Lancaster County - Brunstetter, Wanda E.; Brunstetter, Wanda E.; Brunstetter, Wanda E.; Brunstetter, Wanda E.; Brunstetter, Wanda E.; Brunstetter, Wanda E.; Brunstetter, Wanda E. (Uhrichsville, Ohio : Shiloh Run Press, 2014)
It was to be a short trip to Indiana that might help Like Stoltzfus build a business that would support his young wife. But when Meredith hears that the bus her husband was on burned in a snow-induced accident and his personal effects were found among the rubble, she is left without hope. Harboring a secret she had planned to share when he returned, she must find a way to go on alone. In a Philadelphia hospital, a battered man is brought in from being mugged in a bus station, but his memories have been wiped clean. His caregivers and new friends call him Eddie, but even as his body heals, his soul ongs for a missing part locked away in his injured brain. As the seasons pass from winter to spring to summer, Meredith moves in with her parents and slowly allows old friend Jonah Miller to make her smile again. But even while life must go on, Meredith grieves. Follow the journeys Meredith and Eddie take, and see the miraculous way their lives are brought together.
Goodbye to yesterday -- The silence of winter -- The hope of spring -- The pieces of summer -- A revelation in autumn -- A vow for always.
Keywords: Widows -- Fiction; Amnesia -- Fiction; Amish -- Fiction; Lancaster County (Pa.) -- Fiction